Direct measurement of matrix metalloproteinase activity in 3D cellular microenvironments using a fluorogenic peptide substrate - Leight, Jennifer L. (2013)
Incorporation of degradable moieties into synthetic hydrogels has greatly increased the utility of these three-dimensional matrices for in vitro cell culture as well as tissue engineering applications. A common method for introducing degradability is the inclusion of oligopeptides sensitive to cleavage by matrix metalloproteinases (MMPs), enabling cell-mediated remodeling and migration within the material. While this strategy has been effective, characterization and measurement of cell-mediated degradation in these materials has remained challenging. There are 20+ MMP family members whose activity is regulated in space and time by a number of biochemical and biophysical cues. Thus, the typical approach of characterizing cleavage of degradable moieties in solution with recombinant enzymes does not easily translate to three dimensional cell-mediated matrix remodeling. To address this challenge, we report here the synthesis of a cell-laden hydrogel matrix functionalized with a fluorogenic peptide substrate to provide real-time, quantitative monitoring of global MMP activity. Using this system, stimulation of MMP activity was observed with growth factor treatment in mammary epithelial cells and compared to classical zymography results. Further, the effect of biophysical cues on MMP activity of human mesenchymal stem cells was also investigated where more rigid hydrogels were observed to increase MMP activity. The regulation of MMP activity by these biochemical and biophysical cues highlights the need for in situ, real time measurement of hydrogel degradation, and use of these functionalized hydrogels will aid in future rational design of degradable synthetic hydrogels for in vitro cell studies and tissue engineering applications.